Formation of pyrite in the process of fine coal desulfurization by microwave enhanced magnetic separation. Issue 3 (4th March 2023) - Zhang, Zhenxing; Wei, Xinyu; Yan, Guanghui; Guo, Junwei; Zhao, Pengfei; Yang, Fan; Zhao, Hongyu; Zhang, Bo
ABSTRACT: Coal desulfurization, one of the important research objectives of clean coal technology, has been attracting great importance globally, especially by coal producing and coal consuming countries. Developing clean coal preparation technology before combustion is of great significance to decrease the pollutant emission to the environment and promote efficient and clean utilization of coal energy resource. This study investigated the effect of feed size of – 0.5 mm (finer than 0.5 mm, similarly hereinafter) size pulverized coal, microwave treatment time, and the transformation law of pyrite was characterized by X-ray diffraction (XRD) and X-ray phosphorescence technology (XPS). The results show that with increasing microwave treatment time, the pyrite in the pulverized coal is first transformed into pyrrhotite and then troilite. The order of magnetism in these coal products is as follows: Pyrrhotite > Troilite > pyrite. In addition, the specific magnetization of fine coal first increases and then decreases. With decreasing particle size, the specific magnetic susceptibility X 0 of fine coal decreases gradually; however, the desulfurization degree, Srej, increases gradually. The desulfurization degree of – 0.074 mm fine coal is twice that of the coal particles with the size in the range 0.3–0.5 mm. Magnetic separation of pulverized coal effectively enhanced the desulfurization effect.